Impact of reappropriation of open educational resources on distance and online language teaching - Helène Pulker (Centre National d'Enseignement à Distance, 2020)
Open Education Resources (OER) as the future of online and distance teaching and learning has been a topic of discussion by scholars for some time. In the last 15-20 years, researchers have mainly focused on the creation, reuse and sharing of OER, and little attention has been given to teachers' practices with OER. To date, there is scant evidence of OER reuse impacting on teaching practices, particularly in the context of distance education. This paper presents the findings of a doctoral study which aimed to examine the activities that online and distance language teachers engage with while adapting OER. Data were collected and analysed within a constructivist grounded theory methodology via seventeen semi-structured online interviews. Conceptual categories for the analysis of data were allowed to emerge, rather than initially driven by a theoretical framework. The paper presents the five-step reuse process that emerged from the data analysis with particular emphasis on the reappropriation and learning and developing steps. The paper stresses the significance reuse of OER has for language teaching practices in the context of distance education and raises the question whether OER reuse can lead to significant changes in teaching practices.